The influence of work family conflict on turnover intention mediated by burnout on gen-Z employees in Pontianak - Revialdo, Nathanael; Ginting, Sunardi (International Enterprise Integration Association, 2025)
The high rate of turnover intention among Generation Z, especially in Pontianak City, is a serious concern for organizations, as it can disrupt work stability and productivity. One of the main factors that trigger the intention to leave a job is the conflict between work and family roles (Work-Family Conflict), which often leads to burnout. This study aims to analyze the effect of Work-Family Conflict on Turnover Intention, either directly or indirectly through the mediation of burnout. This research uses a quantitative approach with 152 Gen Z respondents who work in Pontianak City, and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through WarpPLS 8.0 software. The results showed that Work-Family Conflict has a positive and significant effect on Burnout, and both Work-Family Conflict and Burnout have a significant positive effect on Turnover Intention. In addition, burnout also proved to be a significant mediating variable in the relationship between Work-Family Conflict and Turnover Intention. These findings provide important implications for organizations in designing work policies that support work-family balance and burnout prevention strategies to reduce turnover intention among young employees.